Pulmonary aspiration of sinus secretions in patients with cystic fibrosis. Issue 3 (6th December 2017) - Nelson, Jacob; Karempelis, Peter; Dunitz, Jordan; Hunter, Ryan; Boyer, Holly
Abstract : Background: Indirect evidence suggests that sinonasal secretions are aspirated into the lungs of patients with cystic fibrosis (CF), contributing to infection, subsequent tissue damage, and decreased lung function. Our objective is to determine whether sinonasal secretions are transferred to the lungs in patients with CF‐related sinus disease and healthy subjects, particularly in the recumbent position and during sleep. Methods: We performed a prospective, controlled trial to detect pulmonary aspiration of radiolabeled albumin applied to the nasal mucosa of study subjects with chronic sinusitis related to CF and control subjects without sinus disease. Radioactive counts were measured in the lungs and compared to background counts in both groups after 8 hours of rest/sleep. Results: Complete data was collected on 12 CF patients and 6 controls. Eleven patients with CF demonstrated higher lung counts than background counts. The average counts of radiolabeled albumin in the lungs of CF patients were significantly greater than background counts ( p = 0.03). Controls did not demonstrate this finding ( p > 0.90), with only one‐half demonstrating lung counts greater than background counts. Conclusion: This study provides direct evidence of aspiration of sinonasal secretions into the lungs of patients with CF and healthy adults in the recumbent position. The fact that both patients and controls aspirated secretions suggests that aspiration alone does not account for the pathogenesis of lung disease in CF patients.